Tailoring the Mechanical and Antimicrobial Properties of PLA Bioplastics Through Chitosan and Citronella Oil Additives - Safitri, Aida; Raihan, Raudhatul (Politeknik Negeri Lhokseumawe, 2025)
This study investigates the effect of varying chitosan concentrations on the mechanical properties of polylactic acid (PLA)-based films modified with citronella essential oil as an antimicrobial agent. Characterization results indicate that the incorporation of chitosan at 3–5 wt% relative to PLA enhances the tensile strength of the material. This improvement is attributed to the formation of intermolecular hydrogen bonds between the hydroxyl groups of chitosan and the ester groups of PLA, which strengthen the film structure. However, the addition of citronella essential oil to the system significantly reduces the tensile strength. This reduction is associated with the poor compatibility between the essential oil and the PLA–chitosan matrix. Scanning electron microscopy (SEM) analysis revealed the presence of oil droplet agglomerations within the matrix, acting as stress concentration points that weaken the film's mechanical integrity. Such phenomena have been widely reported in PLA-essential oil composite systems. Regarding antimicrobial activity, all films containing both chitosan and citronella oil exhibited significant inhibitory effects against Staphylococcus aureus (Gram-positive) and Escherichia coli (Gram-negative). This antimicrobial efficacy is attributed to a synergistic mechanism, involving the electrostatic disruption of bacterial cell membranes by chitosan and the cytotoxic effects of citronella constituents such as citronellal and geraniol, which penetrate and damage microbial cell walls. Key words: PLA, chitosan, citronella essential oil, Escherichia coli, Staphylococcus aureus.